The Students’ Perception on the Use of QuillBot in Improving Writing - Luthfiyatun Nafisah; Hartono Hartono; Kurniawan Yudhi Nugroho; Mega Mulianing Maharani (Universitas Islam Sultan Agung, 2025)
Writing is not an easy task. Students often have difficulties in writing articles or essays. Many students experience difficulties in grammar and in choosing the correct words to express meaning. Today artificial intelligence-based tools are available to be used to help students in writing. One of them is QuillBot. That digital tool is popular among students nowadays. This research investigates EFL students’ perception in the use of QuillBot to improve their writing. It adopts a mixed-method research design. The respondents of this study were 30 students of an English Education Study Program at a university in Semarang in the 5th semester and 7th semester. The quantitative data collected by giving questionnaire to the respondents while the qualitative data collected through doing semi-structured interviews with five students. The quantitative data was analyzed quantitatively using SPSS, while the qualitative data was analyzed by qualitative thematic analysis. The results of this research from the quantitative data shows that most of students gave positive responses that QuillBot greatly helps them in improving writing skill. Although, some students also use other AI and not make QuillBot as the first choice when it comes to writing, they still use QuillBot but not frequently. Moreover, the interviews confirm the quantitative data that the digital tool is indeed beneficial to use by students. The benefits of using QuillBot are improve grammar skill, enhance vocabulary, improve organizing text skill, more time efficient and give emotional support such as make them more confident in writing. Those aspects are matter to assist students master writing skill.